2020
DOI: 10.15562/phpma.v8i1.249
|View full text |Cite
|
Sign up to set email alerts
|

"I want what they're eating": College students' experiences in watching food content on YouTube

Abstract: Background and purpose: The prevalence of obesity among adolescents is increasing significantly. One of the predictors of this problem is unhealthy eating pattern due to peer and social media influence. This study aims to explore in depth the experience of college students in watching food content on YouTube.Methods: This study used a qualitative method with a phenomenological approach. Data were obtained through in-depth interviews with ten informants and one focus group discussion with seven female students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
0
0
1
Order By: Relevance
“…The results of the current study show that more than 45.5% of participants use YouTube and Facebook regularly, and they also like food pages and occasionally buy food online. Comparing the findings, a study explored college girls" experiences related to watching food content on YouTube (15). The results suggested that the girls found themselves prone to select unhealthy foods after watching food content or food influencers on YouTube.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the current study show that more than 45.5% of participants use YouTube and Facebook regularly, and they also like food pages and occasionally buy food online. Comparing the findings, a study explored college girls" experiences related to watching food content on YouTube (15). The results suggested that the girls found themselves prone to select unhealthy foods after watching food content or food influencers on YouTube.…”
Section: Discussionmentioning
confidence: 99%
“…Teenagers can get influenced by such content and may unknowingly reshape their food preferences. It is evidenced that the people who follow food content on YouTube are more likely to spend money for buying food than those who do not follow such content (15) Young adults particularly face challenging times owing to their educational and academic commitments. Failure to adjust to new challenges can lead to anxiety, stress, and sleep disturbance (16).…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu mukbang juga meningkatkan konsumsi makanan di luar dan pembelian makanan via delivery selama pandemi. (26) Selain mukbang, beberapa video yang memberikan sajian terkait dengan makanan juga bermunculan dan menjadi tren di kalangan remaja dan dewasa muda serta dapat memberikan efek terhadap perubahan kebiasaan makan seperti cookbang, food review, travel, and culinary tour dan ASMR video. (27)…”
Section: Menurut Penelitian Strand and Gustafsson Video Mukbangunclassified